Rethinking Woman-to-Woman Marriage in Udenu Community in Enugu, Nigeria - Cynthia, Eze Celestina; Grace, Ogelenya (Pinisi Journal of Social Science, 2025)
This paper undertakes a Christian critique of woman-to-woman marriage, a cultural institution allowing women to assume the social role of husband to other women for purposes of lineage preservation among the Udenu people of Enugu State, Nigeria. The work examines the general concept of woman-to-woman marriage, investigates its specific manifestation among the Udenu people, identifies the socio-cultural factors that inform the practice, and evaluates the moral questions it raises from a Christian perspective. Using phenomenological and evaluative research methods, the study draws on primary data gathered through oral interviews with traditional rulers, community leaders, and elders, supplemented by published academic sources. The findings contribute to debates about the relationship between African traditional practices and Christian moral frameworks, offering insights into how indigenous institutions navigate tensions between cultural rationality and religious doctrine. The study proposes solutions grounded in Christian theology while acknowledging the legitimate cultural concerns that gave rise to the practice. This work provides valuable knowledge for understanding woman-to-woman marriage at both traditional and theological levels and serves as a resource for addressing the complexities of cultural practice and religious belief in contemporary African societies.